A pre-experimental study to assess the effectiveness of Buerger Allen exercise to improve lower extremity perfusion among patients with diabetes mellitus type 2 admitted to selected hospitals, Jalandhar, Punjab - Parihar, Neha; George, Jophy E. (International Journal Of Community Medicine And Public Health, 2026)
Background: God consider good health one of his greatest gifts. A healthy individual may live a healthy and prosperous life, but many people in the current world cannot owe heart disease, neurological diseases, orthopaedic injuries, and metabolic illnesses, the greatest of which is diabetes. The World Health Organization defines diabetes as a chronic metabolic illness that damages the blood vessels, eyes, kidneys, and nerves due to high blood glucose levels. Methods: This study employed a quantitative research approach with a pre-experimental design (one group pre-test post-test) to evaluate the impact of Buerger Allen Exercise (BAE) on lower extremity perfusion in 60 patients with type 2 diabetes mellitus from selected hospitals. Data collection utilized the Modified Ankle Brachial Index and a self-structured lower extremity perfusion scale. Results: Pre-test mean lower extremity perfusion scores using the Modified Ankle Brachial Index were 1.73 (±0.54) for the right limb and 1.70 (±0.497) for the left limb. Post-test scores significantly improved to 0.53 (±0.72) for the right limb and 0.50 (±0.70) for the left limb, with‘t’ values of 13.59 and 14.69, respectively (p<0.05). Similarly, pre-test scores using the self-structured scale were 14.28 (±3.44) for the right leg and 14.08 (±2.71) for the left leg, improving to 6.88 (±3.26) and 6.98 (±3.01) post-test, with 't' values of 16.36 and 15.86, respectively (p<0.05). Conclusions: The study concludes that Buerger Allen Exercise significantly improves lower extremity perfusion in patients with type 2 diabetes mellitus.